Metode Memperoleh Ilmu Huduri Menurut Mulla Sadra - Fathul Mufid (AL-TAHRIR, 2012)
Epistemological discourse of ilmu h}ud}u>ri> (knowledge by presence), according to the history of Islamic thought, has emerged in the Islamic world before Mulla> S}adra>, particularly among Muslim Peripatetic in one side, with Illumination philosophers, ‘irfa>ni>’thought, and sufi philosophers in other side. These paradigm differences, according to the history, create differences in epistemological concept of ilmu h}ud}u>ri> which ends on truth claim, and affect on continued polemics. Mulla> S}adra> in his intellectual career has encountered this kind of epistemological polemics. This research aims to describe Mulla> S}adra>’s frame of epistemological thought of ilmu h}ud}u>ri> in the midst of the epistemological polemics. The findings are, that Mulla> S}adra>’s typology of philosophical thought on ilmu h}ud}u>ri> is h}ikmah, that is an association between rational and mystical vision, which then is in harmonic with syariah.